Effect Of Area Specific Mineral Supplementation In Anoestrous Cross Bred Heifers - Puvarajan, B.; Vijayarajan , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A Study was conducted to evaluate the effect of supplementation Area specific mineral mixture and iodised salt in concentrate for 30 days to induce ovulatory oestrous on 166 anoestrous crossbred heifers in rural hamlets of Madurai District . After supplementation 92.16% heifers (153/ 166) exhibited oestrous. Of these 149( 97.38%) conceived with 1 to 4 insemination. The first conception rate was 28.18 per cent and second insemination have maximum conception rate (65.77%).However ,progressive decrease in conception rate was observed from third to fourth insemination. The overall conception rate was 27.17 per cent.
Keywords: Area specific mineral mixture; Heifers; Conception rate